PEMANFAATAN KOSAKATA VIRAL SEBAGAI STRATEGI PENULISAN JEBAKAN KLIK DALAM SINIAR - Unggul Putro Sambodo; Sailal Arimi (Universitas Hasanuddin, 2023)
This study aims to explain the use of viral vocabulary as a keyword in a strategy of creating clickbait in a podcast video. This study employed a descriptive qualitative methodology. The data are the linguistic features in the title and thumbnail of the podcast videos as well as the number of views it gets obtained from the Deddy Corbuzier and CURHAT BANG Denny Sumargo YouTube channels that was taken from July to December 2022 using reading and note-taking techniques. The process of data analysis consisted of selecting the vocabulary associated with a viral issue as a clickbait keyword. Then, the data will be compared with the 2022 search trend results. The study's findings indicate a connection between the use of viral keywords in clickbait and the amount of views a podcast video receives. The choice of keywords and when to utilize them are crucial factors in getting viewers.